Creating the built environment an introduction to the practicalities of designing, constructing, and owning buildings - Holes, Leslie (E & FN Spon, 1997)
The purpose of this book is to explain what buildings are and to provide an integrated overview of how they are built and sustained. It does not presume any specialist knowledge.